Erosive effect of an antihistamine-containing syrup on primary enamel and its reduction by fluoride dentifrice - C. C. COSTA, I. C. S. ALMEIDA, & L. C. COSTA FILHO (Paediatric Dentistry, 2006)
This study evaluated the action of an antihistamine-containing syrup (Claritin D) on enamel that was subsequently submitted or not to applications of fluoride dentifrice.